Combination of cytokine-directed and anti-programmed cell death protein 1 therapy – a new attractive option in melanoma treatment?. Issue 5 (October 2018) - Urbonas, Vincas; Smailyte, Giedre
Abstract : The use of monoclonal antibodies against programmed cell death protein 1 (anti-PD-1) has markedly transformed the management of melanoma. However, only a minority of patients treated with anti-PD-1 therapy show a response to therapy and some of them develop immune-related adverse events that can be managed with steroids or anticytokine therapy. A recent study published in Nature Communications has reported that treatment with anti-PD-1 in a tumor necrosis factor-deficient environment may lead to higher response rates to immunotherapy by reducing tumor-infiltrating lymphocytes death, accumulating dendritic cells within cancer, and downregulating T-cell immunoglobulin and mucin-domain-containing-3 expression. This research provides the first proof-of-concept of combining immunotherapy and anti-tumour necrosis factor-α in the melanoma treatment.